Decline of increased risk donor offers increases waitlist mortality in paediatric heart transplantation. (25th August 2021) - Ezekian, Jordan E.; Mulvihill, Michael S.; Ezekian, Brian; Cox, Morgan L.; Kirmani, Sonya; Hill, Kevin D.
Abstract: Background: Increased risk donors in paediatric heart transplantation have characteristics that may increase the risk of infectious disease transmission despite negative serologic testing. However, the risk of disease transmission is low, and refusing an IRD offer may increase waitlist mortality. We sought to determine the risks of declining an initial IRD organ offer. Methods and results: We performed a retrospective analysis of candidates waitlisted for isolated PHT using 20072017 United Network of Organ Sharing datasets. Match runs identified candidates receiving IRD offers. Competing risks analysis was used to determine mortality risk for those that declined an initial IRD offer with stratified Cox regression to estimate the survival benefit associated with accepting initial IRD offers. Overall, 238/1067 (22.3%) initial IRD offers were accepted. Candidates accepting an IRD offer were younger (7.2 versus 9.8 years, p < 0.001), more often female (50 versus 41%, p = 0.021), more often listed status 1A (75.6 versus 61.9%, p < 0.001), and less likely to require mechanical bridge to PHT (16% versus 23%, p = 0.036). At 1- and 5-year follow-up, cumulative mortality was significantly lower for candidates who accepted compared to those that declined (6% versus 13% 1-year mortality and 15% versus 25% 5-year mortality, p = 0.0033). Decline of an IRD offer was associated with an adjusted hazard ratio for mortality of 1.87 (95% CI 1.24, 2.81, p < 0.003). Conclusions: IRD organ acceptance is associated with a substantial survival benefit. Increasing acceptance of IRD organs may provide a targetable opportunity to decrease waitlist mortality in PHT.